2000
DOI: 10.7589/0090-3558-36.4.713
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIATION OF DORSAL-SPINED ELAPHOSTRONGYLINE LARVAE BY POLYMERASE CHAIN REACTION AMPLIFICATION OF ITS-2 of rDNA

Abstract: Molecular genetics was used to devise the first reliable diagnostic tool for differentiating morphologically indistinguishable dorsal-spined, first-stage larvae (L1's) and other stages of the nematode protostrongylid subfamily Elaphostrongylinae. A polymerase chain reaction (PCR) assay employing specifically designed primers was developed to selectively amplify DNA of the ITS-2 region of the ribosomal gene. Amplification of the entire ITS-2 region differentiated between larvae of the genera Elaphostrongylus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…Differences in the second internal transcribed spacer (ITS-2) of ribosomal DNA have been used to identify many nematode parasites (Gasser and Monti, 1997;Criscione et al, 2005), including specimens of DSLs among elaphostrongylines and other protostrongyles (Gajadhar et al, 2000). Restriction digestion of this locus, however, has proven to be equivocal, and it has now been demonstrated that direct sequence comparisons are required to differentiate among species of Parelaphostrongylus if the ITS-2 is the basis for identification .…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the second internal transcribed spacer (ITS-2) of ribosomal DNA have been used to identify many nematode parasites (Gasser and Monti, 1997;Criscione et al, 2005), including specimens of DSLs among elaphostrongylines and other protostrongyles (Gajadhar et al, 2000). Restriction digestion of this locus, however, has proven to be equivocal, and it has now been demonstrated that direct sequence comparisons are required to differentiate among species of Parelaphostrongylus if the ITS-2 is the basis for identification .…”
Section: Introductionmentioning
confidence: 99%
“…The second internal transcribed spacer (ITS-2) of the ribosomal (r) DNA was used as the target to define speciesspecific markers. However, in the study by Gajadhar et al, 5 PCR analyses involving larval samples were based on the amplification of DNA prepared from pools of 25 L 1 s because of the difficulty in isolating sufficient and pure DNA template from individual L 1 s, which vary in size from 308 to 490 m long by 16 to 24 m wide. 13 Adequate recovery of gDNA from individual elaphostrongyline larvae has been a major constraint in the development of reliable PCR assays for the diagnosis of infection.…”
mentioning
confidence: 99%
“…13,14 Development of diagnostic techniques for the accurate identification of individual elaphostrongyline larvae is important for epidemiological studies and the control of these parasites because they differ in their pathogenicity, host specificity, and geographic distribution. 13 A recent study by Gajadhar et al 5 demonstrated the value of polymerase chain reaction (PCR)-based techniques for the identification of elaphostrongyline nematodes to the species level. The second internal transcribed spacer (ITS-2) of the ribosomal (r) DNA was used as the target to define speciesspecific markers.…”
mentioning
confidence: 99%
“…Infections of P. tenuis in WTD can be identified by detecting dorsal-spined larvae in feces followed by polymerase chain reaction (PCR) assay (Gajadhar et al, 2000). However, this method is of little value for detecting infected moose since few ever pass larvae.…”
Section: Introductionmentioning
confidence: 99%